Investigation of Changes in Nucleated Red Blood Cells in Neonatal Infection - Hassan Boskabadi; Mohammad Hadi Sadeghian; javad sadeghinasab (Mashhad University of Medical Sciences, 2017)
Background: Early diagnosis is paramount to the treatment of neonatal infections. Nucleated red blood cells (NRBCs) are immature erythrocytes that increase in number due to stress and hypoxia. This study was conducted to determine NRBC count in the peripheral blood and examine its significance as a marker of neonatal infection. Methods: This case-control study was conducted on 154 infants (78 infants with infection as the case group and 76 infants without infection as the control group) admitted to Ghaem and Emam Reza hospitals, Mashhad, Iran. After a complete physical examination, a series of tests, including blood culture, complete blood count, C-reactive protein test, and peripheral blood smear, were performed on the infants; their NRBCs per 100 white blood cells (WBCs) were also counted. Results: The mean NRBC counts in the infants with and without infection were 30 and 3 per 100 WBCs, respectively (P